Role of proline in cell wall synthesis and plant development and its implications in plant ontogeny - Kavi Kishor, Polavarapu B.; Hima Kumari, P.; Sunita, M. S. L.; Sreenivasulu, Nese (Frontiers in Plant Science, 2015)
Proline is a proteogenic amino acid and accumulates both under stress and non-stress conditions as a beneficial solute in plants. Recent discoveries point out that proline plays an important role in plant growth and differentiation across life cycle. It is a key determinant of many cell wall proteins that plays important roles in plant development. The role of extensins (EXTs), arabinogalactan proteins (AGPs) and hydroxyproline- and proline-rich proteins (H/PRPs) as important components of cell wall proteins that play pivotal roles in cell wall signal transduction cascades, plant development and stress tolerance is discussed in this review. Molecular insights are also provided here into the plausible roles of proline transporters modulating key events in plant development. In addition, the roles of proline during seed developmental transitions including storage protein synthesis are discussed.